1986
DOI: 10.1099/00221287-132-11-3025
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Sequencing of a Gene from Bacillus amyloliquefaciens that Complements Mutations of the Sporulation Gene spoIID in Bacillus subtilis

Abstract: A segment of DNA from Bacillus amyloliquefaciens, which complemented a mutant sporulation gene, spoIID68, in Bacillus subtilis, was cloned into a derivative of the temperate bacteriophage phi 105. The segment of DNA included an entire structural gene and complemented the mutation spoIID298, in addition to spoIID68, in B. subtilis. The nucleotide sequence of the gene from B. amyloliquefaciens was determined and compared with that of the B. subtilis gene; 74% homology was found in the coding region. Amino acid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Computer analysis (IDEAS sequence analysis system on the NBRF protein data base, Release 25.0, Kyushu University, Japan) revealed that CwbA exhibits significant amino acid sequence homology with the B. subtilis and B. amyloliquefaciens spoIID gene products (LopezDiaz et al, 1986;Turner & Mandelstam, 1986) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Computer analysis (IDEAS sequence analysis system on the NBRF protein data base, Release 25.0, Kyushu University, Japan) revealed that CwbA exhibits significant amino acid sequence homology with the B. subtilis and B. amyloliquefaciens spoIID gene products (LopezDiaz et al, 1986;Turner & Mandelstam, 1986) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Difficulties have also been encountered when attempting to clone fragments of DNA larger than about 2.5 kbp in certain plasmid vectors (Gryczan & Dubnau, 1982). Plasmids containing inserts often exhibit structural or segregational instability (see, for example, Bron & Luxen, 1985), even in recipients which are Rec- (Tanaka, 1979;Uhlen et al, 1981;Hahn & Dubnau, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…amyloliquefaciens and B. subtilis, finding that they are very similar in both nucleotide sequence and inferred primary protein structure (Turner and Mandelstam, 1986).…”
Section: Sporulationmentioning
confidence: 94%